An Innovative Technique for Craniocaudal Pedicle Screw Guidance: A Technical Note. Issue 4 (December 2018) - Yadav, Sanjay; Singh, Saurabh
Abstract : In spine surgery, pedicle screw instrumentation is being used very commonly. However, putting pedicle screws in the right place and direction needs the use of image intensifier in 2 orthogonal planes. This consumes valuable time while moving the image intensifier and operating table multiple times during the surgery and also excess radiation exposure. Here, we present a simple technique to apply surgical pearl to angulate the pedicle screws in cephalocaudal direction using simple instrument available on table. This may help in reducing the usage of image intensifier and expedite the procedure.